Why do students plagiarise? Informing higher education teaching and learning policy and practice. Issue 9 (2nd September 2022) - Ayton, D.; Hillman, C.; Hatzikiriakidis, K.; Tsindos, T.; Sadasivan, S.; Maloney, S.; Bragge, P.; Diug, B.; Illic, D.
ABSTRACT: Several interventions have been implemented across higher education institutions with the aim of reducing the prevalence of plagiarism internationally, yet research dedicated to understanding the situational and contextual factors that contribute to plagiarism in an Australian context has been minimal. The objectives of this study were to explore the experiences, views, and understandings of plagiarism from the perspectives of students and teaching staff, and to identify the perceived barriers and enablers of 'ethical' academic writing. The Capabilities, Opportunities, Motivations, and Behaviour (COM-B) model was used as the theoretical framework for this study. Semi-structured interviews and focus groups were conducted with 37 undergraduate students and seven university teaching staff recruited across four health-related academic disciplines within Australia's largest university to elicit their perceptions of plagiarism and the factors that contribute to its prevalence. A total of 16 themes were identified and divided across the Capabilities, Opportunities, and Motivations domains of the COM-B model. Each of the themes within these three domains were classified as either a barrier or enabler of ethical academic writing. The findings reported herein provide the basis of several recommendations for intervention through teaching practice and university policy change to reduce the prevalence of plagiarism within higher education institutions.